2017
DOI: 10.3847/1538-4357/aa7d4f
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Features of the Outer Heliosphere Due to Coupling between the Interstellar and Heliospheric Magnetic Field. V. The Bow Wave, Heliospheric Boundary Layer, Instabilities, and Magnetic Reconnection

Abstract: The heliosphere is formed due to interaction between the solar wind (SW) and local interstellar medium (LISM). The shape and position of the heliospheric boundary, the heliopause, in space depend on the parameters of interacting plasma flows. The interplay between the asymmetrizing effect of the interstellar magnetic field and charge exchange between ions and neutral atoms plays an important role in the SW-LISM interaction. By performing three-dimensional, MHD plasma / kinetic neutral atom simulations, we dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 141 publications
(173 reference statements)
7
92
2
1
Order By: Relevance
“…The magnetic field behavior beyond the HP is determined by the interstellar magnetic field (ISMF) draping over the HP as a tangential discontinuity that separates the solar wind (SW) from the LISM. The simulations of Pogorelov et al (2009aPogorelov et al ( , 2017b; Borovikov & Pogorelov (2014) predicted the magnetic field behavior very similar to observations. The recent simulation of Kim et al (2017) shows that the ISMF "undraping" is consistent with the time-dependent processes occurring in the SW.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The magnetic field behavior beyond the HP is determined by the interstellar magnetic field (ISMF) draping over the HP as a tangential discontinuity that separates the solar wind (SW) from the LISM. The simulations of Pogorelov et al (2009aPogorelov et al ( , 2017b; Borovikov & Pogorelov (2014) predicted the magnetic field behavior very similar to observations. The recent simulation of Kim et al (2017) shows that the ISMF "undraping" is consistent with the time-dependent processes occurring in the SW.…”
Section: Introductionsupporting
confidence: 74%
“…It was crossed in about 1 month, which gives width of about 0.3 AU. There are strong indications that this "structure" is due to the HP instability (Borovikov & Pogorelov 2014) or magnetic reconnection (Schwadron & McComas 2013;Pogorelov et al 2017b), or both.…”
Section: Introductionmentioning
confidence: 99%
“…Webb et al (1986) already showed the importance of Mach numbers for cosmic ray acceleration in MHD models and Scherer et al (2015b) used for simplicity the parameters derived from the heliosphere. In this study, we, for the first time, have shown the Mach numbers to determine the shock structure or even its existence: If the fast magnetosonic Mach number of the ISM is lower than one, no bow shock will exist as discussed for the heliosphere (Pogorelov et al 2017b). The Mach numbers also are used to determine the MHD shock type, especially for the existence of a fast or possible slow shock.…”
Section: Discussionmentioning
confidence: 95%
“…A detailed analysis of the KH in the case of the heliosphere is given by Ruderman & Brevdo (2006), where the authors show that the magnetic field stabilizes the astropause. The feature of a smooth astropause is mainly seen in heliospheric simulations (for example Pogorelov et al 2017a) and in the 3D MHD astrosphere simulations by Katushkina et al (2018) and Gvaramadze et al (2018). Most of the instabilities are discussed in detail for the heliosphere, a special astrosphere.…”
Section: The Stability Of the Astropause And Shocks In (M)hd Simulationsmentioning
confidence: 98%
“…Second, the sector structure was not periodic, since the "sizes" (durations) of sectors varied. It is also possible that therewere ripples on the current sheet (Burlaga & Ness 1994), and we should allow for the possibility that the HCS might be patchy as a result of magnetic reconnection on theoretical grounds (Pogorelov et al 2017). …”
Section: Sector Structurementioning
confidence: 99%